You are on page 1of 4

By: Ben Bishop

a2 = b2 + c2 - 2bcCos(A)
B (x , y)
c
a
y
x
(0 , 0) A b C (b , 0)
• To do this I used the distance formula: √((x2 – x1)2 + (y2 – y1)2)
a = √((x - b)2 + (y - 0)2)
a2 = (x - b)2 + (y - 0)2

• Looking back at the triangle, x can be written as: cCos(A)


because Cos(A) = x/c

• Using the same reasoning, y can be written as: cSin(A)

• So a2 = (x - b)2 + (y - 0)2 becomes: a2 = (cCos(A) – b)2 + (cSin(A))2


a2 = c2Cos2(A) – 2bcCos(A) + b2 + c2Sin2(A)

a2 = c2(Cos2(A) + Sin2(A)) + b2 – 2bcCos(A)

a2 = c2 + b2 - 2bcCos(A)